Dialogue Summary: Enhancing Patient Transitions From Treatment in a Regional Cancer Centre to Survivorship in the Community - Lavis, JN (My University, 2011)
A summary of what was learned from a stakeholder dialogue that addressed problems related to cancer care, options for addressing these problems, key implementation considerations, and next steps for enhancing patient transitions from treatment in a regional cancer centre to survivorship in the Hamilton Niagara Haldimand Brant community.
Keywords: patient; treatment; regional; cancer; community